O século XIX abre as portas para a educação: o ensino de língua portuguesa no Colégio Pedro II - Salino, Emerson (2012)
Under the History of Linguistic Ideas, this project has as the main goal to describe the teaching of Portuguese Language during Brazilian Empire, with emphasis on High School offered by Colégio Pedro II, whose educational programs were adopted by other schools in Brazil. It was followed by apprpriation and representation criteria that were proposed by Chartier (1990) through what the reality can be understood by the discourses, ways and images where the people express themselves and the world. After we can do a picture of the educational aspects in Brazilian Empire, focusing the construction of schools, the impacts caused by the Independence of Brazil and the institutionalization of educational programs and ways of teaching, it was made a more detailed analysis of educational programs in High School courses at Colégio Pedro II , due to the teaching of Portuguese Language. Concluding, the teaching of Portuguese Language was, mainly, tightly linked to the teaching of grammar, which was influenced by the positive scientific rules between 1880 and 1930, and that its main function was to graduate the high society that woul lead the future of the country